Shift of CTX‐M genotypes has determined the increased prevalence of extended‐spectrum β‐lactamase‐producing Escherichia coli in south‐western Sweden. (27th November 2012) - Helldal, L.; Karami, N.; Florén, K.; Welinder‐Olsson, C.; Moore, E. R. B.; Åhrén, C.; Cantón, R.
Abstract The prevalence of Escherichia coli producing extended‐spectrum β‐lactamases (ESBLs) markedly increased during 2004–2008 in south‐western Sweden, with a greater increase in urinary isolates in hospitals (0.2–2.5%) than in the community (0.2–1.6%). ESBLs of genotype CTX‐M predominated, with a significant (p <0.02) shift from the CTX‐M‐9 to CTX‐M‐1 phylogroup occurring among urinary ESBL‐producing E. coli isolated early (n = 41) as compared with late (n = 221) in the study period. The increase in ESBL‐producing E. coli was polyclonal, and only partly attributable to an increase (0–24%) in the number of O25b‐ST131 isolates carrying CTX‐M‐15. The increase was prominent in men and in elderly patients, and warrants continued surveillance.